Influence of food texture on energy metabolism and adiposity in male rats. Issue 10 (13th August 2018) - Han, Wanxin; Utoyoma, Maiko; Akieda‐Asai, Sayaka; Hidaka, Ayano; Yamada, Chihiro; Hasegawa, Kazuya; Nunoi, Hiroyuki; Date, Yukari
Abstract : New Findings: What is the central question of this manuscript ? What is the effect of food texture on fat accumulation, lipogenesis and proinflammatory factors in the adipose tissue and on energy balance in male rats? What is the main finding and its importance ? Calorie intake and fat accumulation in rats fed soft pellets ad libitum increased, but their body weight did not. The data suggest that, even when BMI is normal, frequent consumption of soft food may contribute to the development of lifestyle‐related diseases. Abstract: Dietary factors such as food texture are known to affect feeding behaviour and energy metabolism. We recently found that rats fed soft pellets (SPs) on a 3 h restricted feeding schedule showed glucose intolerance, insulin resistance with disruption of insulin signalling, and hyperplasia of pancreatic β‐cells, even though there were no differences in energy intake and body weight between rats fed control pellets (CPs) and rats fed SPs. We investigated the effect of food texture on fat accumulation, lipogenesis and proinflammatory factors in the mesenteric fat, as well as on energy balance in male rats fed CPs or SPs. We used 7‐week‐old Wistar rats that were randomly divided into two groups, ad libitum fed either CPs or SPs for 27 weeks. Body weight and calorie intake were monitored once a week throughout the experiment. The calorie intake, lipogenesis and fat accumulation of the rats fed SPs increased, whereas their body weight did not. Additionally, SP rats used their fat mainly as a source of energy and increased their energy expenditure. Our data suggest that the habit of frequently eating soft food causes visceral fat accumulation without an increase in body weight. Further investigations using soft‐textured foods could lead to the development of appropriate interventions for non‐overweight patients with lifestyle‐related diseases. Abstract :